Motivasi Masyarakat dalam Mengikuti Olahraga Senam Aerobik di Kabupaten Kudus - Pradevi, Tita; Priyono, Bambang (Indonesian Journal for Physical Education and Sport, 2023)
This research aims to find out the picture of the level of community motivation in following aerobic gymnastics in the holy regency. Considering the recent development of sports is very rapid and the many choices of sports that are in demand to fill daily leisure time. This type of research is quantitative research with descriptive shortness. The location of this study was conducted in Kudus Regency with this research sample is the community that participated in participating in aerobic gymnastics. The data collection technique in the study used questionnaires on a likert scale. Data analysis used includes validity tests, reliability and quantitative descriptive statistics. The results showed the level of community motivation in participating in aerobic gymnastics in Kudus Regency as many as 35 people (35%) belonged to a very high category, and as many as 65 people (65%) had motivation in participating in aerobic gymnastics in Kudus Regency included in the high category. So that it can be concluded that the level of community motivation in following aerobic gymnastics in Kudus Regency falls into the high category. As for the indicators that dominate the most community motivation in following aerobic gymnastics in Kudus Regency, namely physiological needs